T-cell activation is an immune correlate of risk in BCG vaccinated infants - Helen A. Fletcher (Nature Portfolio, 2016)
BCG vaccine confers only partial protection against tuberculosis. Here the authors show that the risk of tuberculosis infection and progression to disease in BCG-immunized children positively correlates with the frequency of activated HLA-DR+CD4+T cells.